ROLE OF LEKHANA VASTI WITH VARAADI KWATHA IN STHAULYA W. S. R TO OBESITY-A PILOT STUDY - Chaitanya, Amrutha; Sadanandam, Ch. (International Journal of Ayurveda and Pharma Research, 2015)
Obesity is a multi-factorial disorder, which is often associated with many other diseases such as DM, HTN, CHD, OA, infertility etc., In Ayurveda Sthaulya has been described since very early days. Susrutha described Lekhana vasti which can be used in Sthaulya. In present study Lekhana vasti with Varaadi kwatha was used to evaluate its role in case of Sthaulya. Methodology: Obese Patients were selected from O.P.D & I.P.D of Dr.B.R.K.R.Govt. Ayurvedic College, Hyderabad, on the basis of wt, BMI, body circumferences etc., 2 cycles of Lekhana vasti were given to each selected patient in form of 9 days 1 Anuvasana in between 3 Lekhana vasti with gap of 10 days in between two cycles. Results: The assessment of overall effect of therapy was done based on change in relevant examinations before and after treatment, and results found were encouraging. Conclusion: However still now there is no effective medicine in modern medicine. So, mankind hopes to search the perfect remedy from Ayurveda by its holistic approach. In this present study Lekhana vasti with Varaadi kwatha was tried and significant results were found in case of Sthaulya.